2018
DOI: 10.1098/rsbl.2018.0262
|View full text |Cite
|
Sign up to set email alerts
|

Sexual attractiveness and reproductive performance in ageing females of a coccoid insect

Abstract: Female age strongly influences reproductive success in various animals. Males are, therefore, expected to show preferential responses to sexual signals released from females of ages suitable for reproduction. Here, however, we report an unexpected and contradictory effect of ageing on sexual attractiveness and reproductive performance in a coccoid insect: the pheromone-based attractiveness of females increased with ageing, though their reproductive performance was in rapid decline. Surprisingly, senescent fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Among the factors that influence the fate of offspring, the role of parental age is currently attracting considerable attention (see Lemaître & Gaillard, 2017 for a review). Evidence of a decrease in reproductive performance at old age has accumulated in the last decades (Nussey, Froy, Lemaitre, Gaillard, & Austad, 2013), and empirical studies have reported evidence of reproductive senescence in a large range of reproductive traits including clutch size (Tabata & Teshiba, 2018), juvenile mass or size (Barks & Laird, 2016; Sharp & Clutton‐Brock, 2010), offspring survival (Packer, Tatar, & Collins, 1998), offspring reproduction (Ducatez, Baguette, Stevens, Legrand, & Fréville, 2012) or offspring lifespan (Barks & Laird, 2016; Lansing, 1947). Interestingly, when Lansing (1947) published his pioneering study demonstrating a negative effect of parental age on offspring lifespan in rotifers, he made no explicit distinction between the maternal and paternal ages.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors that influence the fate of offspring, the role of parental age is currently attracting considerable attention (see Lemaître & Gaillard, 2017 for a review). Evidence of a decrease in reproductive performance at old age has accumulated in the last decades (Nussey, Froy, Lemaitre, Gaillard, & Austad, 2013), and empirical studies have reported evidence of reproductive senescence in a large range of reproductive traits including clutch size (Tabata & Teshiba, 2018), juvenile mass or size (Barks & Laird, 2016; Sharp & Clutton‐Brock, 2010), offspring survival (Packer, Tatar, & Collins, 1998), offspring reproduction (Ducatez, Baguette, Stevens, Legrand, & Fréville, 2012) or offspring lifespan (Barks & Laird, 2016; Lansing, 1947). Interestingly, when Lansing (1947) published his pioneering study demonstrating a negative effect of parental age on offspring lifespan in rotifers, he made no explicit distinction between the maternal and paternal ages.…”
Section: Introductionmentioning
confidence: 99%